Improving FEC layer frame for DVB-S2 link system based on 5G NR polar coding - Omar M Salih; Ashwaq Q Hameed (Bulletin of Electrical Engineering and Informatics, 2023)
Within the scope of this investigation, the MATLAB simulation code for digital video broadcasting–for satellite–second generation (DVB-S2) has been constructed. Forward error correction (FEC) rates as 3/5, 2/3, and 3/4 across additive white Gaussian noise (AWGN) and Rayleigh fading channels are used to evaluate the system's performance, mainly while working on quadrature phase-shift keying (QPSK), 8-ary phase-shift keying (8PSK), 16-ary amplitude phase-shift keying (16APSK), and 32-ary amplitude phase-shift keying (32APSK) official modulation types. The system's redesign has been achieved to investigate high performance and reliability based on a cascade of new radio (NR) fifth generation (5G) Polar coding with low-density parity-check (LDPC). Some signal-to-noise ratio (SNR) levels were changed when evaluated in contrast to the conventional model. It has been determined that five iterations of the LDPC decoder were performed. In comparison to the traditional model. The proposed design's performance accomplished the highest possible value for reducing the bit error rate (BER) value and investigated better-transmitted power gain for most testing cases.